2008
DOI: 10.1007/s00421-008-0725-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training with different intensities and volumes on muscle fibre enzyme activity and cross sectional area in the m. triceps brachii

Abstract: This study primarily examined how intermittent versus continuous endurance training, using similar or dissimilar volumes, affected muscle fibre enzyme activities in the triceps brachii muscle. Thirty-two subjects performed either intermittent (60% of 1RM) or continuous (30% of 1RM) elbow extensions 3 times week(-1) in a training apparatus. Training was performed until either a low (five) or a high volume (8 weeks) was accumulated. Muscle biopsies from the m. triceps brachii were taken pre- and post training an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
(40 reference statements)
5
16
0
1
Order By: Relevance
“…These properties of the VL were also associated with training volume to which mitochondrial complex protein I was also associated. These relationships might simply be explained by the known effects of endurance training commonly observed on skeletal muscle oxidative capacity in young adults (Gjøvaag & Dahl, ; Hepple, Mackinnon, Goodman, Thomas & Plyley, ; Holloszy & Coyle, ) and the role that these have in influencing endurance cycling performance and aerobic power (Bassett & Howley, ). The findings relating to oxygen uptake kinetics are in general agreement with previous research indicating that the association between oxygen uptake kinetics and type I fibres is in part due to a greater capillarity of type I fibres which reduces the variability in blood flow to, and the transit time through, the working muscle at the onset of exercise (Piiper, ; Pringle et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These properties of the VL were also associated with training volume to which mitochondrial complex protein I was also associated. These relationships might simply be explained by the known effects of endurance training commonly observed on skeletal muscle oxidative capacity in young adults (Gjøvaag & Dahl, ; Hepple, Mackinnon, Goodman, Thomas & Plyley, ; Holloszy & Coyle, ) and the role that these have in influencing endurance cycling performance and aerobic power (Bassett & Howley, ). The findings relating to oxygen uptake kinetics are in general agreement with previous research indicating that the association between oxygen uptake kinetics and type I fibres is in part due to a greater capillarity of type I fibres which reduces the variability in blood flow to, and the transit time through, the working muscle at the onset of exercise (Piiper, ; Pringle et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the all-out nature of the RST would have required the recruitment of a large proportion of type II fibers, whereas ET would require the recruitment of predominantly type I fibers (29). It has been shown that interval training induces greater oxidative enzyme adaptations in type II fibers than continuous training (24,30), and that type IIb fibers manifest greater training-induced elevations in oxidative capacity as training intensity increases above V O 2peak (20). These fiber-type-specific adaptations would be expected to result in faster V O 2 kinetics and enhanced tolerance to high-intensity exercise (12,18,38,44).…”
Section: Exercise Tolerancementioning
confidence: 99%
“…This benefit to longer-duration aerobic performances from a 30-second training regime has been suggested elsewhere (1,15,18) Other mechanisms that contribute to improvements in short-term aerobic performance have been suggested. These include time to fatigue on V _ O 2 max testing without changes in V _ O 2 max and the positive effects of enhanced neuromuscular adaptations postresistance training (17,18). These adaptations may also have occurred in this study.…”
Section: Discussionmentioning
confidence: 70%
“…The greater increase in average weight per repetition and total weight moved on the PO may have resulted from differences in the fiber type composition of the muscles performing these exercises. The fiber composition of the muscles involved in the BP, predominantly the pectoralis major and minor (57% fast twitch) and the triceps brachii (65% fast twitch) (17,19), has a significantly higher fast twitch fiber composition than the muscles used during the PO exercise (latissimus dorsi 50% fast twitch and posterior deltoid 44% fast twitch) (20). This lower fast twitch composition of the muscles recruited during the PO movement suggests that a greater proportion of the ATP demand would originate from oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%